Sustainable technologies adoption research: A weight and meta-analysis. (September 2022) - Neves, C.; Oliveira, T.; Santini, F.
Abstract: Along with escalating environmental problems, the role of technologies in mitigating those problems has also increased. Researchers have been studying the adoption of sustainable technologies, and the number of articles on the topic has grown in recent years. The current study presents a weight and meta-analysis that synthesizes and combines previous literature on sustainable technologies adoption, evaluating the state of the art and providing a comprehensive picture of the phenomena. Using 44 articles and 48 datasets, the results demonstrate that attitude, benefits, personal norms, incentives, and perceived behavioral control are the best predictors of the behavioral intention of sustainable technologies adoption. Moreover, journal ranking, innovation, individualism, and long-term orientation, as cultural moderators, as well as electricity access and renewable energy, as energy efficiency indicators, were found to moderate subjective norms and behavioral intention. The findings of this study are relevant for future research support. Highlights: A weight and meta-analysis on sustainable technologies (ST). Clearer and harmonized view of ST adoption research. Identification of the best and promising indicators of ST behavior intention. Attitude, benefits, personal norms, and incentives as best predictors. Moderation of innovation, cultural and energy efficiency indicators.